Integrating Contrastive Analysis into Classroom in English as Foreign Language Context - Ima Widyastuti; Aura Victoria Noersadono (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2022)
In English as Foreign Language (EFL) countries, learners mostly gain their English knowledge in the classroom and in the limited time. Without strong intrinsic motivation of acquiring English, it would be hard for the learners to reach the language acquisition. Historically, second language acquisition was begun from the contrastive analysis in which the learners compare their first and the second language. Though the study is quite old, however, it is still useful for the truly beginners especially in EFL context. The current conceptual study aims to view the contractive analysis applied in EFL classroom. The implementation of the contrastive analysis in Indonesia cannot be separated from the students’ characteristics, classroom environment, and length of input. The comparative analysis on the sentence types and the Subject – verb agreements underpinned the further analysis on the contrastive analysis between Bahasa and English.